Adoption of Goat Production Technology at the Farm Level: A Case of Krishnagandaki VDC, Shyangja District - Nepali, Megh Bahadur; Sapkota, Sudha; Upreti, Sujaya; Pokhrel, Bhoj Raj; Sharma, Bimala; Devkota, Hari Prasad; Amatya, Sabita Mohini (Nepal Journal of Science and Technology, 2011)
Adoption of goat production technology consists of health, breeding, nutrition, pasture and fodder and management. The study was conducted in Krishnagandaki VDC of Syangja district with the objective of exploring the existing goat production technology adoption at the farm level. The methodology of the study included household survey, participatory rural appraisal and secondary data analysis. Most of the farmers raised goats in the villages. Overall farmers reported that the average adoption of goat production technology was (42.2%). The study revealed that farmers adopted breeding technology (53.5%), health technology (34.8%), nutrition technology (36.2%), management technology (53.9%) and pasture, fodder and agro-forestry technology (32.4%). Key words: breeding; health; nutrition; pasture; management DOI: 10.3126/njst.v11i0.4127 Nepal Journal of Science and Technology 11 (2010) 79-82